Hemming for Joining High Strength Steel Sheets - Zamzuri, Hamedon; Mori, Ken-ichiro; Abe, Yohei (Elsevier Ltd, 2014)
A high strength steel sheet is used to make the hollow sections for the body structure of automobiles. The hollow sections, which are typically joined by resistance spot welding have insufficient energy absorption because the joins are not continuous. Thus, to overcome this problem, the hollow section is joined using the hemming process. The hemming of the high strength steel sheet was successfully performed using punch with stopper. The high strength steel hollow sections joined by hemming and resistance spot welding were then examined by tensile and fatigue tests. The hollow section with hemmed joins showed better performance in both tests. The overlapping joins of the hemmed hollow section have greater strength as compared to the resistance of spot welding joins.